OPTIMIZATION OF CO2 LASER CUTTING PARAMETERS FOR MDF AND HDF WOOD FIBER BOARDS - Magaznieks, Edgars; Narica, Pāvels (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2018)
Laser cutting of medium density fibre board (MDF) and high density fibre board (HDF) is a complicated process and the selection of the process parameters combinations is essential to get the highest quality cut section. A CO2 laser was used to cut two thicknesses 3 mm of laminated HDF and 10 mm of MDF panels.